Synthesis and Characterization of Chicken Bone-Derived Hydroxyapatite Incorporating Pectin - Teoh M.W.; Ng C.K.; Lee K.Y.S.; Singh R.; Ting C.H.; Chuah Y.D.; Lim Y.I.; Tan C.Y.; Yeo W.H. (John Wiley and Sons Inc, 2024)
Hydroxyapatite (HA) was synthesized from chicken bone waste by calcination. Pectin was extracted from orange peels by microwave irradiation, and 1 and 3 wt % of pectin was incorporated into the HA. The resulting powders were then pressed into disk samples before being sintered at temperatures of 1050, 1150, and 1250 C for 2 h. Various analytical techniques, including Fourier transform infrared spectroscopy, X-ray diffraction, scanning electron microscopy, density measurement, and Vickers microhardness tests, were used to evaluate the characteristics and mechanical properties of the samples. The incorporation of pectin did not interfere with the pure phases of HA, and minimal amounts of ?-tricalcium phosphate were detected in the XRD patterns. Both ball milling and the addition of pectin effectively reduced the particle size of HA. However, the addition of pectin above 1 wt % did not contribute significantly to the densification and hardness of chicken bone-derived HA (CHA) compared with ball-milled CHA. Samples sintered at 1050 C had the lowest relative density, owing to incomplete particle fusion. Increasing the sintering temperature resulted in a maximum relative density of ca. 95 % and a Vickers microhardness of 4.12 GPa for ball-milled CHA samples sintered at 1250 C. Sintering temperature and ball milling were observed to play a more significant role in the densification and hardness of CHA compared with the addition of pectin. 2023 Wiley-VCH GmbH.